Delegation And Employee Work Outcomes: An Examination Of The Cultural Context Of Mediating Processes In China - Xiong Chen, Zhen; Aryee, Samuel (Academy of Management Journal, 2007)
We used cultural self-representation theory to develop a model of the processes linking delegation to work outcomes. We tested this model with data from a sample of 171 subordinate-supervisor dyads from the People's Republic of China. Regression results revealed that organization-based self-esteem and perceived insider status fully mediated the influence of delegation on affective organizational commitment, task performance, and innovative behavior and partially mediated delegation's influence on job satisfaction. Furthermore, traditionality moderated the relationships between delegation and the mediators in such a way that the relationships were stronger for individuals lower rather than higher in traditionality.